2023
DOI: 10.1002/advs.202302146
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Blood Cell‐Based Diagnostic Test for Myalgic Encephalomyelitis/Chronic Fatigue Syndrome Using Peripheral Blood Mononuclear Cells

Jiabao Xu,
Tiffany Lodge,
Caroline Kingdon
et al.

Abstract: Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is characterized by debilitating fatigue that profoundly impacts patients' lives. Diagnosis of ME/CFS remains challenging, with most patients relying on self‐report, questionnaires, and subjective measures to receive a diagnosis, and many never receiving a clear diagnosis at all. In this study, a single‐cell Raman platform and artificial intelligence are utilized to analyze blood cells from 98 human subjects, including 61 ME/CFS patients of varying di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The multi-marker environment with complex interlinks requires an AI-based toolkit for decision support. The resulting outcomes when stacking various AI-based decision machines have yet to be determined in the case of ME/CFS [see ( 44 ) for a novel stacking approach]. Clearly, the inflammatome–immunome interaction is a criterion that complements machine-learning-based AI systems as described in ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The multi-marker environment with complex interlinks requires an AI-based toolkit for decision support. The resulting outcomes when stacking various AI-based decision machines have yet to be determined in the case of ME/CFS [see ( 44 ) for a novel stacking approach]. Clearly, the inflammatome–immunome interaction is a criterion that complements machine-learning-based AI systems as described in ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, he has developed a novel Raman spectroscopy approach which examines peripheral blood mononuclear cells (PBMCs), and diagnoses ME/CFS with 90% accuracy based on impaired cellular bioenergetics and dysfunctional mitochondrial profiles. 21 These tests provide diagnostic possibilities and may point to metabolites and metabolic pathways that play a role in the disease pathology.…”
Section: Organ-specific Syndromesmentioning
confidence: 99%
“…Xu et al [ 52 ] proposed a new potential biomarker, phenylalanine, for the diagnosis of ME/CFS using PBMCs and single-cell Raman spectroscopy. More recently, the same group of authors developed a more powerful single-cell Raman platform, combined with artificial intelligence, to analyze blood cells from 98 human subjects, comprising 61 ME/CFS patients with varying disease severity and 37 healthy and MS patients as disease control [ 53 ]. The results demonstrated that Raman profiles of blood cells can accurately distinguish between healthy individuals, disease controls, and ME/CFS patients with high accuracy (91%).…”
Section: Raman Micro-spectroscopy Unveiled: Illuminating Metabolism A...mentioning
confidence: 99%